Essence and characteristics of administrative procedures for the protection of human rights by the Ministry of justice of Ukraine - Krasnohor, Oleksandr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The semantic content of the terms «procedure», «legal procedure» and «administrative procedure» is studied. It is noted that the formation of an understanding of the content and essence of the concept and features of administrative procedures, which are implemented by the Ministry of Justice of Ukraine in the course of protecting human rights, is a success in understanding the general system of administrative procedures as a component of administrative law. It is noted that administrative procedures are an obligatory tool in the functioning of public administration. Scientific views on the content of the concept of «administrative procedure» and the features of this institution of administrative law are analyzed. The legislative definition of the concept of administrative procedure is studied and aspects of its narrowing are highlighted, taking into account scientific views on its content. The author’s definition of the concept of administrative procedures for the protection of human rights by the Ministry of Justice of Ukraine is formed, it is noted that like any process implemented in regulated social relations, the administrative procedure is endowed with certain features that reveal its essence and content. It has been established that the administrative procedure in Ukraine requires substantial revision and improvement. Its legal definition should not be limited solely to the sphere of service provision but must encompass all aspects of interaction between citizens and state authorities. The improvement of the administrative procedure will contribute to strengthening the rule of law, protecting human rights, and enhancing the efficiency of public administration in Ukraine. It is proposed to expand the legal definition of administrative procedure by including mechanisms for appeals, protection of citizens’ rights, and oversight of state authorities’ actions; to harmonize Ukrainian legislation with the principles of the European Charter of Local Self-Government and other international standards; and to strengthen the accountability of officials for violations of administrative procedures to improve the effectiveness of public governance.